Determination of the Incidence of Medical Device-related Pressure Injury in Pediatric Intensive Care Unit: A Single-center Study - Erhan Elmaoğlu; Zerrin Çiğdem; Adnan Batuhan Coşkun; Şule Çevik (Journal of Pediatric Emergency and Intensive Care Medicine)
Introduction: To determine the incidence of pressure injuries caused by medical devices in the pediatric intensive care unit. Methods: It is a prospective study of observational analytical type. Strengthening the Reporting of Observational Studies in Epidemiology guide was used in the study. It was conducted with 117 children in the pediatric intensive care unit of a gynecology and pediatrics hospital in the Southeastern Anatolia Region of Turkey between 01.01.2023 and 30.06.2023. In the study, data were collected using the information form together with the Braden and Braden Q scale. Data were analyzed with SPSS 25.0 statistical analysis program. Results: It was determined that 53% of the children included in the study were male, 24.8% were hospitalized due to neurological diseases, 55.6% had chronic diseases and 74% were fed enterally. It was determined that the average age of the children was 37.46±40.98 (months), the average body weight was 15291.45±17364 (g), and the average height was 83.06±23.85 (cm). In the study, pressure injuries caused by medical devices occurred in 26.5% of the children, 35.7% of these pressure injuries caused by medical devices were 1st degree, 17.6% were ungraded wounds (Mucosa), 48.5% of the children were injured. It was observed that 2 injuries occurred in 100,000 children and 44.4% of the children had 5 or more medical devices. It was determined that the average number of days for injuries caused by medical devices was 38.63±41.91 days, the frequency of injuries per 1000 patient days was 14.98, and the rate of injuries caused by medical devices was 5.9%. Conclusion: The study showed that a high rate of pressure injuries occurred due to medical devices. Appropriate care should be planned for children admitted to pediatric intensive care units by assessing the risk of injury caused by medical devices.